2020
DOI: 10.1186/s12879-020-05397-6
|View full text |Cite
|
Sign up to set email alerts
|

Distribution pattern of amino acid mutations in chloroquine and antifolate drug resistance associated genes in complicated and uncomplicated Plasmodium vivax isolates from Chandigarh, North India

Abstract: Background The increasing antimalarial drug resistance is a significant hindrance to malaria control and elimination programs. For the last six decades, chloroquine (CQ) plus pyrimethamine remains the first-line treatment for P. vivax malaria. Regions where both P. falciparum and P. vivax co-exist, P. vivax is exposed to antifolate drugs due to either misdiagnosis or improper treatment that causes selective drug pressure to evolve. Therefore, the present study aims to estimate antimalarial drug resistance amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
3
12
1
Order By: Relevance
“…Studies in India have also reported this double mutant. A study conducted in Chandigarh also had similar findings with 117/118 isolates (99%) having this double mutant [49]. A multicentric study done by Vamsi et al from different regions of India, such as, Puducherry, Mangaluru, Cuttack and Jodhpur revealed 91.6% of the isolates with mutations, T958M and F1076L [53].…”
Section: Cq-chloroquine In a Wild Type Plasmodium Vivax Infected Rbc ...supporting
confidence: 55%
See 3 more Smart Citations
“…Studies in India have also reported this double mutant. A study conducted in Chandigarh also had similar findings with 117/118 isolates (99%) having this double mutant [49]. A multicentric study done by Vamsi et al from different regions of India, such as, Puducherry, Mangaluru, Cuttack and Jodhpur revealed 91.6% of the isolates with mutations, T958M and F1076L [53].…”
Section: Cq-chloroquine In a Wild Type Plasmodium Vivax Infected Rbc ...supporting
confidence: 55%
“…The molecular markers for chloroquine resistance are mutations in the pvcrt-o and pvmdr1 genes. Insertion of lysine (AAG) at the 10th amino acid position (K 10 insertion) of exon1 of Pvcrt-o is the commonly reported mutation of the pvcrt-o gene and has been reported from India as well [48,49]. However, most of the K10 insertion that has been reported so far was from Myanmar (46-72%) and Thailand (56-89%) [50][51][52].…”
Section: Cq-chloroquine In a Wild Type Plasmodium Vivax Infected Rbc ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Although chloroquine had been discontinued for nearly a decade, a higher abundance of mutated P. falciparum chloroquine-resistant transporter ( pfcrt ) and a lower prevalence of mutated P. falciparum multidrug resistance 1 ( pfmdr1 ), which confer resistance to chloroquine, were observed [ 74 , 75 ]. Mutant alleles of pvmdr1 gene were also observed among P. vivax from New Delhi Capital Region [ 76 ], Chandigarh in North India [ 77 ] and the southwestern coastal region in South India [ 78 ]. The presence of Kelch 13 mutations, which confer resistance to artemisinin-based combination therapy (such as artesunate/sulfadoxine/pyrimethamine), have also been reported from India [ 79 ].…”
Section: Malaria Status Among Countries Contributing Most Of the Imported Malaria Cases In Gcc Countriesmentioning
confidence: 99%